A New Distribution Record of Invasive Mealy Bug, Rastrococcus Invadens (Hemiptera: Pseudococcidae) Infesting Mango (Mangifera Indica) from Nagaland, India - Firake, D. M.; Behere, G. T.; G, Rajesha; Lytan, D.; Deka, B. C. (Indian Journal of Hill Farming, 2016)
An invasive mealy bug, Rastrococcus invadens (Hemiptera: Pseudococcidae) was reported for the first time infesting mango (Mangifera indica) trees from Nagaland, India. About 37.63% of total mango trees were found to have mild to high infestation of R. invadens (N=93) in Medziphema and adjoining areas of Nagaland state. This mealy bug species was previously recorded from few states of India on different host plants and it was only recorded from Sikkim state of North east India.